(3TQM QSGdI GHf CHj RjO GdbjQhGfis - (3JGO GdOjf YeQ Hf Ydj Hf SGde Hf UObI GddNeI GdEScfOQi GdaGcgGfis; (3CHh eMeO YHO Gddg Hf CHj RjO GdeGdcj GdbjQhGfj,J (B389 (3g` s
(3ChdgG (B:s
(3aEf GdcJGH GdeHGQc GdTgjQ HGdQSGdI deG YXe TCfgG ETJgQJ ETJgGQ GdfgGQ , hTGYJ ai LejY GdCbWGQ s
(3BNQgG (B:s
(3bGd dEeQCJg (B: (3Ef de Ccf ef Cgd GdLfI aCfJ WGdb , agi WGdb SGYJFP heKdg Ef de CONd GdLfI ced GdSaQ GdChd s
(3cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdeGdcjs